Chemical Budbreak Induction Methods to Increase Blackberry Yields under Inadequate Chilling Conditions - Shinsuke Agehara; Syuan-You Lin (EDIS)
Blackberry production has recently expanded to the Southeast. In Florida, inadequate winter chill limits blackberry production by causing poor and erratic budbreak. To compensate, we developed chemical budbreak induction methods based on the field trial data collected over 3 growing seasons. This new 4-page article provides guidelines for the budbreak induction methods, with the aim of supporting the development of subtropical blackberry production. Written by Shinsuke Agehara and Syuan-You Lin. https://edis.ifas.ufl.edu/hs1419